2020
DOI: 10.1055/s-0040-1721659
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation in Preterm Neonates with Late-Onset Sepsis: Is It Beneficial?

Abstract: Objective Neonatal sepsis (NS) is a serious neonatal disease. The aim of this study was to detect the role of zinc (Zn) supplementation in preterm neonates with late-onset sepsis (LOS). Study Design A prospective randomized clinical trial study which was done at Tanta University Hospital from August 2016 to March 2018 on 180 preterm neonates with LOS. The studied neonates were divided into two groups: group 1 (90 neonates), which received Zn and antibiotics, and group 2 (90 neonates), which receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Five studies were conducted in India, 2 in Egypt, and one each in Nepal, Pakistan, Bangladesh, and Italy. The study settings included pediatric inpatient wards [25, 27, 29, 30], neonatal ICUs [18, 19, 24, 26, 28, 32], and the community [31]. The characteristics of included studies are as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were conducted in India, 2 in Egypt, and one each in Nepal, Pakistan, Bangladesh, and Italy. The study settings included pediatric inpatient wards [25, 27, 29, 30], neonatal ICUs [18, 19, 24, 26, 28, 32], and the community [31]. The characteristics of included studies are as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum sample size reported was 72 children [30] and the maximum population size was 700 children [25]. Eight [18, 19, 24-27, 29, 32] of the included studies reported the therapeutic effect of zinc supplementation, whereas only 3 studies [28, 30, 31] evaluated the preventive efficacy of the zinc supplement. We report below the preventive and therapeutic effects of zinc supplementation in neonates and young infants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Zinc in human milk, like phosphorus and calcium, might not have been ideal for extremely preterm newborns and feedings of human-milk should be supplemented with extra zinc for this population, according to evidence. 12,13 Marthur et al (2015) 14 at Maulana Azad Medical College, New Delhi, India, studied the effects of zinc supplementation on the growth of premature newborns. They observed that (those receiving oral zinc supplementation) had significantly greater mean serum alkaline phosphatase levels than the controls at 3 months corrected age.…”
Section: Introductionmentioning
confidence: 99%